2018
DOI: 10.1016/j.jmii.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of herpes zoster in human immunodeficiency virus-positive patients initiating combination antiretroviral therapy in Taiwan

Abstract: Herpes zoster occurred in 6.5% of HIV-positive Taiwanese patients after initiation of cART, which was associated with prior zoster and baseline CD4 count < 200 cells/μL or baseline PVL > 5 log copies/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The included studies were from Asia ( n = 44), Northern America ( n = 20), Europe ( n = 13) and the Middle East ( n = 3). Most studies were from Taiwan ( n = 30) [ 40 , 41 , 43 , 44 , 50 , 54 , 58 63 , 68 , 76 79 , 81 , 83 85 , 87 , 90 , 96 98 , 100 , 104 , 105 , 115 ] and the US ( n = 19) [ 36 , 37 , 39 , 46 , 47 , 55 , 57 , 64 , 73 , 75 , 80 , 88 , 89 , 99 , 101 , 102 , 106 , 112 , 113 ]. In sum a total study population of 796,796,295 was included, with 10,904,736 HZ cases reported in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were from Asia ( n = 44), Northern America ( n = 20), Europe ( n = 13) and the Middle East ( n = 3). Most studies were from Taiwan ( n = 30) [ 40 , 41 , 43 , 44 , 50 , 54 , 58 63 , 68 , 76 79 , 81 , 83 85 , 87 , 90 , 96 98 , 100 , 104 , 105 , 115 ] and the US ( n = 19) [ 36 , 37 , 39 , 46 , 47 , 55 , 57 , 64 , 73 , 75 , 80 , 88 , 89 , 99 , 101 , 102 , 106 , 112 , 113 ]. In sum a total study population of 796,796,295 was included, with 10,904,736 HZ cases reported in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, the only marker of CMI assessed clinically is CD4 count which is associated with development of HZ but not always predictive. For example, a higher prevalence of HZ has been observed in those with VL suppression and CD4 > 750 cells/μL compared to HIV-uninfected persons [ 1 , 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although our study showed no association between VZV antibody levels and clinical HZ in an HIV-infected population, we validated findings from prior studies demonstrating that that lower CD4 count and lack of ART use were risk factors for the development of HZ. Other risk factors described in this population include high VL and prior history of HZ [ 6 , 7 ]. In order to reduce the morbidity associated with HZ in HIV-infected persons, additional clinical markers of risk are needed as well as VZV vaccine safety and efficacy studies in younger patients with preserved CD4 counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation